THE EFFECT OF INTEGRATING LITERATURE INTO SECOND LANGUAGE CLASSROOMS ON STUDENT ENGAGEMENT IN HIGHER EDUCATION INSTITUTIONS (Scientific journal of the Fergana State University, 2025)
This article explores the impact of integrating literature into second language (L2) classrooms on student engagement in higher education institutions. A review of existing literature reveals that the inclusion of literary texts enhances cognitive, emotional, and social engagement, fostering a more holistic learning experience.